PENGARUH KUALITAS PELAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH PENGGUNA MOBILE BANKING PT. BANK NEGARA INDONESIA TBKDI KCP BUARAN JAKARTA - Hendrik Tri Laksono Putro; Thamrin Thamrin; Samsudin Samsudin (JAMBIS : Jurnal Administrasi Bisnis, 2021)
At present competition between banks are very competitive, both in the national market and global market. that is a challenge must be faced and handled by all banking companies. The demand for sophisticated information technology facilities in the present and the future are banking challenge to provide the best service to the public. The purpose of this study is to analyze how much influence the service’s quality have on customer satisfaction at Buaran Sub-Branch Office BNI Bank. The research type used in this study is a quantitative concrete because it can be quantified in the form of numbers. The sample in this study were 100 respondents.The Data analysis techniques in this study used descriptive analysis techniques and simple linear analysis. Service Quality positively influences Customer Satisfaction. This is evidenced by the significant results of 0,000 <0,05 which means that there is an influence between Service Quality partially on Customer Satisfaction. It means that BNI always strives to improve the Indicators of Service Quality for Mobile Banking Applications used by BNI customers so that simultaneously the services’ Quality provided will be able to meet or satisfy the needs and desires to reuse Mobile Banking customers to form a positive attitude towards the Quality of Mobile Banking Service